Leptin and Melanocortin Signaling Mediates Hypertension in Offspring From Female Rabbits Fed a High-Fat Diet During Gestation and Lactation - Lim, Kyungjoon; Burke, Sandra L.; Marques, Francine Z.; Jackson, Kristy L.; Gueguen, Cindy; Sata, Yusuke; Armitage, James A.; Head, Geoffrey A. (Frontiers in Physiology, 2021)
Maternal high-fat-diet in rabbits leads to hypertension and elevated renal sympathetic nerve activity (RSNA) in adult offspring but whether this is due to adiposity or maternal programming is unclear. We gave intracerebroventricular and ventromedial hypothalamus (VMH) administration of leptin-receptor antagonist, α-melanocyte-stimulating-hormone (αMSH), melanocortin-receptor antagonist (SHU9119) or insulin-receptor antagonist to conscious adult offspring from mothers fed a high-fat-diet (mHFD), control diet (mCD) or mCD offspring fed HFD for 10d (mCD10d, to deposit equivalent fat but not during development). mHFD and mCD10d rabbits had higher mean arterial pressure (MAP, +6.4mmHg, +12.1mmHg, P<0.001) and RSNA (+2.3nu, +3.2nu, P<0.01) than mCD, but all had similar plasma leptin. VMH leptin-receptor antagonist reduced MAP (-8.0±3.0mmHg, P<0.001) in mCD10d but not in mHFD or mCD groups. Intracerebroventricular leptin-receptor antagonist reduced MAP only in mHFD rabbits (P<0.05). Intracerebroventricular SHU9119 reduced MAP and RSNA in mHFD but only reduced MAP in the mCD10d group. VMH αMSH increased RSNA (+85%, P<0.001) in mHFD rabbits but intracerebroventricular αMSH increased RSNA in both mHFD and mCD10d rabbits (+45%, +51%, respectively, P<0.001). The insulin-receptor antagonist had no effect by either route on MAP or RSNA. Hypothalamic leptin-receptor and brain-derived-neurotrophic-factor mRNA were greater in mHFD compared with mCD rabbits and mCD10d rabbits. In conclusion, the higher MAP in mHFD and mCD10d offspring was likely due to greater central leptin signaling at distinct sites within the hypothalamus while enhanced melanocortin contribution was common to both groups suggesting that residual bodyfat was mainly responsible. However, the effects of SHU9119 and αMSH on RSNA pathways only in mHFD suggest a maternal HFD may program sympatho-excitatory capacity in these offspring and that this may involve increased leptin receptor and brain-derived-neurotrophic-factor expression.